2016
DOI: 10.1097/mpg.0000000000001007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Natural History of Celiac Disease in a Cohort of At‐risk Children

Abstract: Prevalence of CD in this cohort was 4%, half of whom had digestive symptoms. Because a high proportion of children showed a spontaneous disappearance of antibodies, prevalence studies of CD in young children should be based on intestinal damage so as not to overestimate results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 39 publications
0
24
0
2
Order By: Relevance
“…G.I related diseases include celiac disease which was the most common disease presented to outdoor patient which was found to be 17.8%, where as in an another study it was found to be 7%, which was low In comparison [3] , furthermore there were also underdiagnosed cases of celiac disease, similarly tissue transglutaminase were positive in 61.1% of the patients with celiac disease in our study, whereas Trovato. CM et al in his study reported that paediatric patients with seropositive TTG were 68.5% [13] , patients with the celiac disease develop polyautoimmunity [14] , Unusual high rate of incidence of celiac disease has been reported in study conducted at Sweden, during 40 year time period 1030 patients have celiac disease [15] , another article reported the prevalence of celiac disease which is found to be 4.1% [16] , whereas its frequency among children of Germany is found to be 0.9% [3] .…”
Section: Discussionmentioning
confidence: 99%
“…G.I related diseases include celiac disease which was the most common disease presented to outdoor patient which was found to be 17.8%, where as in an another study it was found to be 7%, which was low In comparison [3] , furthermore there were also underdiagnosed cases of celiac disease, similarly tissue transglutaminase were positive in 61.1% of the patients with celiac disease in our study, whereas Trovato. CM et al in his study reported that paediatric patients with seropositive TTG were 68.5% [13] , patients with the celiac disease develop polyautoimmunity [14] , Unusual high rate of incidence of celiac disease has been reported in study conducted at Sweden, during 40 year time period 1030 patients have celiac disease [15] , another article reported the prevalence of celiac disease which is found to be 4.1% [16] , whereas its frequency among children of Germany is found to be 0.9% [3] .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of Celiac disease is 2%-3% in Finland and Sweden, 0.2% in Germany [15], 1.6% in Asia [16], and 1% in the United States [17]. The prevalence was 4% in a recent study by Cilleruelo et al [9] who used the HLA-DQ2 test [9]. This variability in the worldwide prevalence can be attributed to differences in the type of test used for screening, sample size, age, and criteria for celiac disease diagnosis among studies [18,19].…”
Section: Introductionmentioning
confidence: 92%
“…Celiac disease is diagnosed on the basis of clinical symptoms; serological tests for the detection of serum immunoglobulin (Ig) A (IgA), TTG antibody, and IgA-endomysial antibody; and histopathological examination of biopsy specimens from the intestinal mucosa [6,7]. Recently, genetic studies identifying HLA DQ2/DQ8 antigens have been utilized more frequently [8], because the spontaneous disappearance of antibodies over time has been observed in a proportion of children with Celiac disease [9]. Approximately 83% patients remain undiagnosed or are misdiagnosed, which can result in irreversible medical and dental complications [10].…”
Section: Introductionmentioning
confidence: 99%
“…Small intestinal biopsy was offered to those who tested positive for IgA-tTG [IgA-tTG > 20 relative units (RU)/mL]. [ 1 ] Since a proportion of children with CD have been shown to have a spontaneous disappearance of antibodies over time,[ 2 ] I presume that significant percentage of potentially silent CD were missed from Al Hatlani's study. (2) The consumption of wheat containing gluten as a major staple food is still a common custom in the Kingdom of Saudi Arabia (KSA).…”
mentioning
confidence: 99%